Odpowiedź:
8300%
Szczegółowe wyjaśnienie:
1. Pierwsza liczba [tex](a^{2}+a^{\frac{1}{2} } )*a^{-2}[/tex]
2. Druga liczba [tex]a^{-2}[/tex]
Zakładam , że liczba a = 9 i obliczam :
1. [tex](9^{2}+9^{\frac{1}{2} } )*9^{-2}[/tex] = (81 +[tex]\sqrt{9}[/tex]) * [tex]\frac{1}{9^{2} }[/tex] = ( 81 + 3) * [tex]\frac{1}{81}[/tex] = 84 * [tex]\frac{1}{81}[/tex] = [tex]\frac{84}{81}[/tex]
2. [tex]9^{-2} = \frac{1}{9^{2} } = \frac{1}{81}[/tex]
([tex]\frac{84}{81}[/tex] : [tex]\frac{1}{81}[/tex])* 100% = ( [tex]\frac{84}{81} * \frac{81}{1}[/tex] ) * 100% =84 * 100% = 8400 %
Jeżeli liczba druga stanowi 100% to liczba pierwsza jest od niej większa o:
8400% - 100% = 8300%